(untitled) (Research, Society and Development, 2020)
This academic work had as goal to analyze the dynamics of the action from a social net which operates in the third sector field, supporting and strengthening the institution that sustain people who are in social vulnerability in the county of Ijuí/RS – Brazil, as well as to comprehend what are the perspectives of the social actors involved. As theorical referential, the concepts of the Net Theory and Third Sector oriented this study, what allowed the researchers to deepen their knowledge about this theories, which provided the general analysis of this study. This research, from interpretative feature and essentially qualitative, is built in case study, with technical triangulation of data collect and analysis methods, using quizzes with open questions in likert scale, having as subjects the social actors that participate in the net; documental analysis and the participant observation due to the action of the researcher in the net through the period of 2 and a half years. The results of the research allowed identifying that the net is formally constituted, and that is saw as very valuable to the strengthening of the associated entities, where the actions allow a higher visibility to this ones. However, it was also found verified that the current Covid-19 pandemic situation, has been being harmful and challenging to the full development of the net activities and its associates.